2007
DOI: 10.1590/s0004-27302007000500006
|View full text |Cite
|
Sign up to set email alerts
|

Expressão das iodotironinas desiodases nas neoplasias tireoidianas

Abstract: RESUMOAs iodotironinas desiodases formam uma família de selenoenzimas com propriedades catalíticas distintas que ativam ou inativam os hormônios tireoidianos via desiodação do anel fenólico ou tirosínico da molécula do T4. As desiodases tipo I e II (D1 e D2) são as enzimas responsáveis pela geração do T3 e são amplamente expressas na tireóide normal. A transformação neoplásica benigna ou maligna da glândula tireóide está associada a alterações na expressão dessas isoenzimas, sugerindo um possível papel da D1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
4
0
1
Order By: Relevance
“…In contrast, type 3 iodothyronine deiodinase (DIO3, D3) catalyzes the inactivation of T 4 and T 3 via inner ring deiodination . Several studies have shown an association between thyroidal status and tumor pathogenesis (Pinto et al 2011, Kim & Cheng 2013 while several reports have documented changes in the expression of deiodinases in benign and malignant tumors (Huang et al 2001, Murakami et al 2001, de Souza Meyer et al 2005, Dentice et al 2007, Meyer et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, type 3 iodothyronine deiodinase (DIO3, D3) catalyzes the inactivation of T 4 and T 3 via inner ring deiodination . Several studies have shown an association between thyroidal status and tumor pathogenesis (Pinto et al 2011, Kim & Cheng 2013 while several reports have documented changes in the expression of deiodinases in benign and malignant tumors (Huang et al 2001, Murakami et al 2001, de Souza Meyer et al 2005, Dentice et al 2007, Meyer et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a growing number of studies indicate that deiodinase expression is also altered in cancer (previously reviewed in Meyer et al, 2007; Piekielko-Witkowska and Nauman, 2011). While it is conceivable that deiodinase expression is unrelated to the cancer process, there is good indication that deiodinase reactivation could in some cases constitute a useful marker of the disease (Gereben and Bianco, 2009; Piekielko-Witkowska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal D2 expression and function have been described previously in other human neoplasms (Curcio et al, 2001;Dentice et al, 2007;Meyer et al, 2007;Morimura et al, 2005). Indeed, it is conceivable that thyroid status is linked to the development and growth of neoplastic tissues (Lemaire et al, 1981;Leuthauser et al, 1987).…”
Section: Discussionmentioning
confidence: 90%